Affects of Working Capital Management on Firm’s Performance: Evidence from Bangladesh - Datta, Rajib; Barua, Sujoy; Mawa, Jannatul (Archives of Business Research, 2023)
Working capital is a proportion of an organization’s liquidity and monetary wellbeing which assesses the performance and profitability of an organization inside a limited period. The ceramic business is one the most troublesome and lengthy process industry comparing other industries. This industry is immense and includes bigger cycle which makes challenges to present the performance with genuine information. This paper is an attempt to investigate the affects of working capital management on firm’s performance of ceramic industries in Bangladesh. For this intent, ceramic corporations enrolled in Dhaka Stock Exchange (DSE) & Chittagong Stock Exchange (CSE) have been chosen and the investigation covers a period from year 2016 to 2021. Accordingly, secondary data from reputed ceramic manufacturers listed on DSE & CSE have been chosen to outline the measurable impacts of working capital management, also execution of firms by utilizing dynamic board information investigation. The results demonstrates that, inventory and cash conversion cycle periods are longer than expected. Also the industry is highly dependent on accrued sales and receiving cash from the sales are longer comparing other industry. The study clearly defines the significant level of relationship between the firm’s performances which is affected by different components of working capital management.